2000
DOI: 10.1021/la9909345
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Packing Densities and Surface Order on the Frictional Properties of Alkanethiol Self-Assembled Monolayers (SAMs) on Gold:  A Comparison of SAMs Derived from Normal and Spiroalkanedithiols

Abstract: We report a comparative study of the structure and frictional properties of self-assembled monolayers (SAMs) generated by the adsorption of three homologous 17-carbon alkanethiolssheptadecanethiol, 2,2dipentadecyl-1,3-propanedithiol, and 2-pentadecyl-1,3-propanedithiolsonto the surface of Au(111). The structural properties of these SAMs were characterized by atomic force microscopy, surface infrared spectroscopy, X-ray photoelectron spectroscopy, spectral ellipsometry, and wettability by water and hexadecane. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
158
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 171 publications
(179 citation statements)
references
References 26 publications
21
158
0
Order By: Relevance
“…Clearly the last of these is most relevant to understanding OFMs but the first two provide bettercharacterised, close-packed monolayers. These studies have confirmed the important influence of chain length and packing density on friction and also provided some estimates of film strength [79][80][81]. Most AFM work has studied films on substrates withdrawn from the liquid phase (i.e.…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 68%
“…Clearly the last of these is most relevant to understanding OFMs but the first two provide bettercharacterised, close-packed monolayers. These studies have confirmed the important influence of chain length and packing density on friction and also provided some estimates of film strength [79][80][81]. Most AFM work has studied films on substrates withdrawn from the liquid phase (i.e.…”
Section: Ofm Research 1990s To Presentmentioning
confidence: 68%
“…The chemical and physical properties of a surface will affect the interaction of this adhesive with the surface. Lee et al (2000) reported that shorter, less ordered SAMs The influence of surface lubricity J. Bowen et al 475 exhibit greater frictional forces, as measured using AFM, than crystalline, ordered SAMs, discussing the effect of intermolecular packing on the modulus of the SAM.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al examined the frictional properties of SAMs composed of spiroalkanedithiols, which had the same packing of the anchor group but different packing densities at the sliding interface, and showed that the relative frictional properties of the monolayer films mirrored the trends in packing density and crystalline order of the films [137]. Perry et al also measured the frictional properties of SAMs formed from a series of spiroalkanedithiols and a single structurally related normal alkanethiol, and observed that less densely packed monolayers exhibited higher friction [138].…”
Section: Influence Of Conformational and Structural Disordermentioning
confidence: 99%